The Influence of Islamic Religious Education on Character Building among Seventh-Grade Students at Alwashliyah 8 Junior High School Medan - Nasution, Hasnil Aida; Sari Harahap, Hotni; Azmi, Hanifa; Karim, Muhammad Nasir (Universitas Islam Negeri Raden Intan Lampung, 2025)
Character refers to the fundamental traits inherent in every individual. In today’s generation, core character values, such as honesty, respectful communication, and discipline, are increasingly eroded. Therefore, efforts must be made to restore these values. Within the educational sphere, teachers bear significant responsibility, particularly Islamic Religious Education (IRE) teachers, in cultivating morally grounded and well-charactered students. This study investigates the influence of Islamic Religious Education on character building among seventh-grade students at SMP Alwashliyah 8 Medan. The objective is to examine how IRE contributes to students’ character development. Employing a quantitative associative research design, data were collected through questionnaires, observations, and documentation, and analyzed using descriptive and inferential techniques. The findings reveal: (1) Islamic Religious Education at SMP Alwashliyah 8 Medan is categorized as “good,” with a score of 82%, based on questionnaire responses from 62 participants; (2) students’ character building is rated “very good,” at 89%, based on the same sample; (3) there is a significant influence of IRE on character building, as evidenced by hypothesis testing with a significance value of 0.000 ≤ 0.05, indicating acceptance of Ha and rejection of H0. Furthermore, the effect size shows that IRE contributes 38.4% to character building, while the remaining 61.6% is influenced by other variables not examined in this study.